2018
DOI: 10.3390/ijms19071922
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar GTP-Binding Protein 1-2 (NOG1-2) Interacts with Jasmonate-ZIMDomain Protein 9 (JAZ9) to Regulate Stomatal Aperture during Plant Immunity

Abstract: Plant defense responses at stomata and apoplast are the most important early events during plant–bacteria interactions. The key components of stomatal defense responses have not been fully characterized. A GTPase encoding gene, NOG1-2, which is required for stomatal innate immunity against bacterial pathogens, was recently identified. Functional studies in Arabidopsis revealed that NOG1-2 regulates guard cell signaling in response to biotic and abiotic stimulus through jasmonic acid (JA)- and abscisic acid (AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…A virulent strain of Pseudomonas syringae then injects the phytotoxin, coronatine (COR), which mimics the action of jasmonic acid–isoleucine (JA–ILeu), which is the active form of JA, into the host plant, in order to stimulate the re-opening of the stomata. COR, thus termed an effector, functions by stimulating the biosynthesis of JA via Jai1 , which in turn induces JA–ILeu-inducible wound-responsive genes via the transcription factor, MYC2, while repressing PATHOGENESIS-RELATED ( PR ) genes [ 48 , 49 , 50 ]. Thus, the wounding response becomes activated at the expense of defense response.…”
Section: Aba-mediated Stress Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…A virulent strain of Pseudomonas syringae then injects the phytotoxin, coronatine (COR), which mimics the action of jasmonic acid–isoleucine (JA–ILeu), which is the active form of JA, into the host plant, in order to stimulate the re-opening of the stomata. COR, thus termed an effector, functions by stimulating the biosynthesis of JA via Jai1 , which in turn induces JA–ILeu-inducible wound-responsive genes via the transcription factor, MYC2, while repressing PATHOGENESIS-RELATED ( PR ) genes [ 48 , 49 , 50 ]. Thus, the wounding response becomes activated at the expense of defense response.…”
Section: Aba-mediated Stress Responsesmentioning
confidence: 99%
“…A small GTPase protein, NOG1-2, stimulates stomatal closure during abiotic stresses, and the nog1-2 mutant of Nicotiana benthamiana is more susceptible to the pathogen Pseudomonas syringae , due to its inability to close its stomata [ 55 ], proving its role in the re-closing of stomata opened by Pseudomonas syringae . NOG1-2-mediated stomatal closure is stimulated in the presence of COR, indicating that its function is dependent on JA–Ileu [ 48 ]. In Arabidopsis, JAZ9 is the protein that interacts with MYC2 and COI1 through its JA-associated (Jas) domain [ 56 ].…”
Section: Aba-mediated Stress Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…f. glauca were probably the member of transcription factor families like WRKY, GH3, TIFY/JAZ, CML, ERF, TGA. Coincidently, it has been reported that above transcription factors did be widely involved in various defense responses [58,[90][91][92][93][94][95][96][97][98][99][100][101][102]. It is reported that GH3 and CML can also regulates fruit development [103,104].…”
Section: Resistance Genes (R Genes)mentioning
confidence: 87%
“…f. glauca were probably the member of transcription factor families like WRKY, GH3, TIFY/JAZ, CML, ERF, TGA. Coincidently, it has been reported that above transcription factors did be widely involved in various defense responses [26,[66][67][68][69][70][71][72][73][74][75][76][77][78]. It is reported that GH3 and CML can also regulates fruit development [79,80].…”
Section: Resistance Genes (R Genes)mentioning
confidence: 87%